2022
DOI: 10.3390/nu14235194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in Patients with Parkinson’s Disease: A Systematic Review

Abstract: Objectives: This systematic review analyzed the prevalence of malnutrition in patients with Parkinson’s Disease. Study design: a systematic review. Method: Four databases—Cochrane, PubMed, Embase and Web of Science—were searched from October 2021 to June 2022 by two independent researchers. The inclusion criteria were as follows: patients above 18 years old with confirmed Parkinson’s Disease, performed screening nutritional assessment, cohort studies, case-control studies, and cross-sectional studies. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The rates of malnutrition and risk of malnutrition observed in elderly inpatients with PD were higher than those reported in community-dwelling elderly patients [6,14]. A systematic review indicated malnutrition rates of 0% to 2% and malnutrition risk rates of 20% to 34% in PD [15]. In our study, among the 48 participants, 10 (20.8%) were malnourished and 26 (54.2%) were at risk of malnutrition, indicating an overall higher incidence compared to patient with PD in the previous study.…”
Section: Discussionmentioning
confidence: 81%
“…The rates of malnutrition and risk of malnutrition observed in elderly inpatients with PD were higher than those reported in community-dwelling elderly patients [6,14]. A systematic review indicated malnutrition rates of 0% to 2% and malnutrition risk rates of 20% to 34% in PD [15]. In our study, among the 48 participants, 10 (20.8%) were malnourished and 26 (54.2%) were at risk of malnutrition, indicating an overall higher incidence compared to patient with PD in the previous study.…”
Section: Discussionmentioning
confidence: 81%
“…For example, research revealed an inverse relationship between the intake of coffee and caffeine and the likelihood of PD ( 33 ). Another investigation indicated that consuming a diet abundant in fruits, veggies, legumes, whole grains, poultry, and fish was associated with a reduced risk of PD ( 34 ). A different meta-analysis indicated that adhering to a Mediterranean eating style, which involves consuming ample amounts of fruits, vegetables, and fish, was linked to a decreased occurrence of PD ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss and increased energy expenditure (due to motor symptoms) are associated with PD. 41 The present verse denotes PD associated with complications and mortality.…”
Section: Nikashanniva --Hitam Bahu (Verse 12)mentioning
confidence: 99%